The Study of Sigapiton Tourism Village Development Through the Pentahelix Model, Ajibata District, Toba Regency - Bahagia Tondang (Politeknik Pariwisata Medan, 2021)
The aim of this study is to see and analyze Pentahelix elements’ role and contribution in developing Sigapiton Tourism Village. The research approach is qualitative descriptive method that starts from the observation, documentation study and interview with the informants that are familiar with the helixes’ roles and contributions to the development of Sigapiton Tourism Village. Sigapiton Village is included in the list of four villages in the National Tourism Strategic Area (KSPN) of Lake Toba. The result of the study shows that the elements of Pentahelix as stakeholders need to carry out activities and programs seen as essentials and significant in developing Sigapiton Tourism Village. The result of the study also shows that not every helix did their roles and contributions as expected. This leads to the stagnation of the development of Sigapiton Tourism Village. The result of this stagnation may be one of the main reasons behind the low visit rate of the Sigapiton Tourism Village.